Antimicrobial resistance of Escherichia coli from broilers in large-scale poultry farms in Shandong Province - Liu, Xiaoxia; Li, Xiang; Liu, Jing; Chen, Ruiying; Liu, Rui; Zhao, Ruting; Zhao, Jia; Hao, Jianwei; Yang, Shuming; Luo, Aiguo; Chen, Ailiang (Frontiers in Microbiology, 2025)
BackgroundAntimicrobial resistance (AMR) is a global challenge affecting both healthcare and agricultural fields, as emphasized by the World Health Organization (WHO). Industrial poultry production plays a crucial role in the development and dissemination of AMR. A comprehensive understanding of the molecular mechanisms underlying AMR is imperative for developing effective control strategies.Materials and methodsThis study aimed to identify factors influencing AMR in Escherichia coli from large-scale commercial broiler farms. Samples, including 371 anal swabs, 95 fecal swabs, and 122 feed-trough swabs, were collected from Cobb broilers at the four production stages (1, 15, 26, and 38 days of age) on typical farms in Shandong Province. From these specimens, 508 E. coli strains were isolated and characterized. Antimicrobial susceptibility was assessed using the Kirby–Bauer disk diffusion method against 15 commonly used antibiotics, and results were interpreted according to CLSI guidelines.ResultsThe resistance rates of the isolated strains varied between 24.41% and 95.47%. A total of 96.45% of the strains exhibited multidrug resistance, and 29 strains were resistant to all 15 antibiotics. The highest resistance was observed against penicillin (amoxicillin and ampicillin), followed by florfenicol, chloramphenicol, tetracycline, cefotaxime, and cefazolin. The lowest resistance was noted for ofloxacin and gentamicin. Drug resistance was most substantial at 15 days of age compared with that at 1, 26, and 38 days of age.DiscussionAn analysis of the relationship between drug resistance and drug use showed that doxycycline significantly increased the resistance rate (68.40%, p < 0.05). Additionally, the drug resistance of bacteria isolated from fecal swabs was higher than that of bacteria from anal and feed-trough swabs. The results indicate that sample type, drug type, and age all influence E. coli drug resistance in poultry, with drug type having the greatest impact.